Utilization of ionic deep eutectic solvent as sustainable mobile phase additive in high‐performance liquid chromatography for improving the separation of biogenic amines. Issue 22 (13th September 2022) - He, Sile; Choi, Dong Min; Row, Kyung Ho
Abstract : Biogenic amines are present in large quantities in fermented foods and are a key marker for assessing food safety. This paper proposes a novel method for high‐performance liquid chromatography analysis of biogenic amines using deep eutectic solvent as a mobile phase additive. After screening eight synthetic deep eutectic solvents and comparing them with several common additives, deep eutectic solvents based on choline chloride and ethylene glycol showed significant effects in improving the separation of biogenic amines. A Box–Behnken design of 17 runs was used to screen and optimize the key chromatographic parameters, resulting in an expected composition of the mobile phase of 0.73% deep eutectic solvent, 65% acetonitrile, and a column temperature of 28°C. The proposed method exhibited excellent linearity (0.1–50 μg/ml, R 2 ≥ 0.9987), limit of detection (0.007–0.031 μg/ml), precision (1.28%–5.34%) and accuracy (87.2%–110.6%). The method can be applied successfully to the separation and analysis of biogenic amines in cooking wine samples.